Diffuse articular chondrocalcinosis - Ana Luisa Vanalle Ferrari; Adil Muhib Samara (Einstein (São Paulo), 2008)
Chondrocalcinosis is a disease caused by joint deposition of calciumphyrophosphate dehydrate crystals, which can lead to many differentclinical presentations. This fascinating disease can occur as recurrentinfl ammatory attacks (Pseudogout), other forms of chronic arthritis(e.g. pseudo RA) or even as assymptomatic form. The primary diseaseoccur mainly in young adults, meanwhile the secondary form isoften associated with osteoarthritis, predominantly in the aged. Diagnosisis made when positively birefringent calcium pyrophosphatecrystals are found in synovial fl uid analysis. X-ray fi ndings can alsohelp, showing radio densities (linear or punctated) in cartilage. Prognosisdepends on the ethiology (if secondary), number of ill joints andseverity. Treatment is based on the use of non-steroidal anti-infl ammatoryand systemic glucocorticoids.